Exploring gene sequences and phylogenetic relationships of four terrestrial planarian species (Platyhelminthes; Tricladida; Geoplanidae) in Europe - Álvarez-Presas, Marta; Littlewood, D. Timothy J.; Mateos, Eduardo; Jones, Hugh D. (Zootaxa, 2023)
Partial mitochondrial cox1 gene sequences from four recently recognised European species of terrestrial planarians, and ribosomal ITS1 sequences for two of them, are presented: Marionfyfea adventor, Artioposthia exulans (both introduced from New Zealand), Australopacifica atrata (from Australia) and specimens putatively identified as Microplana edwardsi, presumed to be native to the UK. The sequences are compared with those from other terrestrial planarian species and analysed phylogenetically. Results indicate that the sister group of M. adventor comprises a clade constituted by at least the genus Arthurdendyus. The phylogenetic position of Ar. exulans remains less certain, Australopacifica atrata might be closely related to the species Parakontikia ventrolineata and Endeavouria septemlineata. The specimens of M. cf. edwardsi are distinct from all other Microplana species for which sequences are available.